Social Learning: Baduy Tribe's Strategy in Maintaining Their Identity Amidst Tourism - Cika Aprilia (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2024)
The life of the Inner Baduy tribe, particularly in Cibeo village, is still coloured by strong customary laws and culture, making it an attraction for tourists. Despite this, the Baduy tribe refused to be a tourist destination in 2020, fearing damage to their culture. They prefer the term 'saba budaya' or gathering rather than tourism as it relates to their 'pikukuh' or customary law. Despite not receiving formal education, the Baduy tribe has a social learning system that is in accordance with their background. This social learning is their identity strategy, even though they do not have formal schooling.This research uses the theories of Li Yang, Theron Nunez, Barth, and Hewlett to analyse the impact, background, positioning, boundary strategy, and social learning of the Inner Baduy tribe towards tourism. The ethnographic method is used to collect data through interviews, observations, literature studies, and documentation. The analysis shows that the Inner Baduy tribe does not reject tourism as long as it does not interfere with their daily activities. Cibeo Village is open to tourism due to the practice of their ancestors. Their position as hosts is supported by WISUBA with mutually beneficial cooperation. However, the impacts of this interaction include cultural commodification and ecological damage, such as plastic waste. Ethnic boundary strategies are used to defend their existence from the impacts of tourism. Social learning plays an important role in maintaining their identity as indigenous people without formal education.